A variety of indicators evaluated for two implementation methods for a Citizen's Basic Income - Malcolm Torry (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Debate about Citizen's Basic Income - an unconditional and nonwithdrawable income for every individual - is shifting in character. An earlier phase related to the proposal's desirability; then followed debate about its feasibility; and now attention is turning to questions of implementation. A significant symptom of this new phase is the recent consultation on implementation of a Citizen's Basic Income held by the Institute of Chartered Accountants in England and Wales. The consultation considered four implementation methods. This working paper operationalises characteristics of two of the implementation models in terms of changes that might be required in existing UK tax and benefits systems, and evaluates the implementation methods in relation to a wider variety of indicators than previous exercises of this kind: poverty and inequality indices, tax rate rises required for revenue neutrality, household disposable income gains and losses, households' abilities to escape from means-testing, and marginal deduction rates. The advent of EUROMOD G4.0+ and updated FRS data enables the results to be more up to date as well as more comprehensive.
Keywords: C80; H53; H55; I38; R20; 330; Citizen's Basic Income; microsimulation model implementation